Perlindungan Hukum Terhadap Persamaan Pemegang Hak Atas Merek Dalam Persaingan Dagang - Henny Novianti; Joko Sriwidodo; Sartono Sartono (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
Regarding the critical nature of trademark reform, Indonesia participated in the World Intellectual Property Organization's approval of the International Trademark Agreement (WIPO). The 1992 Trademark Law was updated in 1997 by Law No. 10 Resolution No. 14 of 1997, which takes into account the provisions of the International Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS-GATT). This clause protects the origin and geographical indicators of products. Additionally, the provision modifies the former in the preceding law. With regards to trademarks in Indonesia Each user has the ability to trademark his or her name. According to Article 3 of Law No. 20 of 2016 on Marks, trademark rights are granted to registered trademark owners, indicating that the brand system in Indonesia is a constitutive (active) system, with registered trademark owners being trademark rights holders. The registered mark's owner, as the mark's holder, either uses the mark himself or grants authorization to others to do so. Additionally, Article 40 of Law No. 20 of 2016 on Marks and Geographical Indications provides that trademark rights may be transferred in accordance with the Act's provisions.